TINGKAT STRES DENGAN GANGGUAN SIKLUS MENSTRUASI REMAJA - Irma Fidora; Yosi Okrira (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Stress was a condition that suppressed the individual that was caused by an imbalance between the capabilities of the existed demands, caused a reaction or response of the body both psychological, physiological and behavioral. Various kinds of emotional changes due to a stressor had associated with hormonal fluctuations during the menstrual cycle. Purpose to determine the relationship between levels of stress and menstrual cycle disorders in young women in SMK Pembina Bangsa Bukittinggi. This study was a non-experimental used correlational descriptive method with cross sectional approach. This research was conducted in June-July 2018. The sample in this studyamounted to 50 people were taken with the used of simple random sampling. Collected data using the questionnaire and analysis using Chi-square to know the relationship between stress levels and menstrual cycle disorders in young women in SMK Pembina Bangsa Bukittinggi. Result: About 38% respondent experienced severe stress levels, (66%) had abnormal menstrual cycles. The results of this study also showed a relationship between the level of stress and menstrual cycle disorders p= 0,018. Conclusion: The result showed a significant relationship between the level of stress and menstrual cycle disorders in young women in SMK Pembina Bangsa Bukittinggi, for it was expected to students in order to tackle the causes of stress that can disrupt the menstrual cycle.